MEMETAKAN JARINGAN TRANSNASIONAL IDEOLOGI KEAGAMAAN DI KALANGAN MAHASISWA PENDIDIKAN ISLAM - Muhammad Raihan (Yayasan An-Nur Meunara Baro, 2025)
This study aims to map the transnational religious ideological networks influencing Islamic Education students in Indonesia. Using Social Network Analysis (SNA) combined with in-depth interviews, the research explores the structural patterns, key actors, and ideological transmission mechanisms involved. Findings reveal that the networks are not random but hierarchically structured, with hub actors acting as bridges to foreign institutions, particularly in the Middle East and South Asia. Social media emerges as a powerful amplifier, accelerating the dissemination of ideological content through visually engaging and easily accessible narratives. Ideologies such as Salafism, the Muslim Brotherhood, and HTI are dominant within these networks, reinforced by active alumni and digital outreach strategies. The study highlights the urgent need for policy-based interventions to promote religious moderation within Islamic Higher Education Institutions (PTKI), focusing on digital media surveillance, ideological literacy, and the revitalization of locally rooted Aswaja narratives. These findings contribute both theoretically and practically to understanding how global ideological flows transform into local influence within religious higher education settings.